Concussion Incidence for Two Levels of Senior Amateur Rugby League in New Zealand, 2008-2011 - King, D; Hume, P; Cummins, C; Clark, TN; Gissane, C (Remedy Publications, 2018)
Aim: To report the incidence, injury mechanisms and assessment of concussion in two levels of amateur senior rugby league over 2008-2011. Methods: A prospective observational study of competition injuries in a New Zealand rugby league domestic club with two levels of participation (amateur representative, amateur premier domestic) between 2008-2011. All injuries were recorded on a standardised injury reporting form. Players were evaluated with the SCAT in 2008, and SCAT-2 in the 2009-2011 seasons as part of the health practitioner assessment. Differences were assessed by player level (club, representative), history of concussion (new, recurrent) and type of play (match, training). Results: There were 43 matches and 434 training sessions resulting in 1,849 matches and 18,279 training exposure hr. There were 40 match-related and seven training-related concussions recorded. Concussion incidence was higher for the amateur representative players (37.2 per 1,000 match-hr) than the amateur premier domestic players (16.1 per 1,000 match-hr). The most common injury mechanism for a concussion was during the tackle to the ball-carrier. When compared with the tackler (5 per 1,000 match-hr), the ball carrier (13 per 1,000 match-hr) recorded three-fold more concussions. Highest concussion incidence occurred in the fourth quarter (38.9 per 1,000 match-hr) of matches. Most concussion injuries occurred in the fourth-quarter and second half of matches. Discussion: Future studies should consider a longitudinal review incorporating recovery time, repeat concussion intervals, and differences in recovery time, for players with recurrent concussions in the same year against repeat concussions over the longitudinal period. What is known about the subject? • The number of concussions that occur in rugby league have varied depending upon the level of participation and the injury definition utilised, • Concussion epidemiology islimited by the lack of empirical data as moststudies are typically on one team for a limited period, • Concussion is typically reported as part of wider studies reporting on the incidence of injuries in match and training rugby league studies. What this study adds to existing knowledge? • At the amateur rugby league level of participation, the incidence of concussion is higher than professional rugby league, • Inclusion of symptom indices can assist with the identification of the distress the concussed player is undergoing as a result of the concussive injury.
Keywords: Rugby league; Concussion; Mild traumatic brain injury; Match; Training